Technological Advances in Dejavu Movie - Matondang, Adira Gautama; Dwiastuty, Nina; Prasetyo, Agung; Miranti, Ira; Muniroh, Zumrotul; Santoso, Doni Anggoro Ari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2025)
The purpose of this study is to find out about technological progress in the film that explains and represents technological progress in the movie Dejavu, namely the development in the scheme and story containing the Theory of Relativity previously proposed by Albert Einstein. This is in several explanations and interpretations of logic, namely the proof of the representation of space and time with electromagnetic wave tools, which are widely available in our environment, although sometimes less realized, for example, an instrument that occurs every time we travel either on foot or by using a vehicle, then the acceleration produced will also be different in space and time. That is an example of an instrument that will be explained through a film work. This research method uses a descriptive qualitative method and uses the Theory of Relativity consisting of Acceleration Relativity, Time Expansion, Lorentz Contraction, and Mass and Energy Relativity. Based on the results of this Dejavu movie research, it can explain in detail how an object can move from one place to another, with a percentage connecting the Theory of Relativity with this Dejavu movie, it is concluded that Acceleration Relativity has 8 scenes (65%), Time Expansion has 3 scenes (15%), Lorentz Contraction has 2 scenes (10%), and Mass and Energy Relativity has 1 scene (5%). Acceleration relativity is present in certain accelerations although from science there are still some things that are still under development, in addition to technological advances based on CGI (Common Gateway Interface) which is a benchmark for combining technology in a film so that the understanding that is done can be conveyed clearly and realistically.